PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY(CRH) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KIMIA SISWA SMA N 1 KOTA BENGKULU - 1Nurul Zulhulaifah; Nurhamidah Nurhamidah; Elvinawati Elvinawati (ALOTROP, 2018)
This study is a classroom action research applying the Course Review Horay learning model on the subject of basic chemical laws and chemical reaction equations in three cycles with four stages: planning, implementation, observation and reflection on each cycle aimed at improving motivation, activity and results learning chemistry of students of class X IPA 5 SMA N 1 Kota Bengkulu academic year 2017/2018. The study was conducted in March-April of 2018 with a total of 27 students, consisting of 17 women and 10 men. The data were obtained using questionnaire of motivation, posttest and observation sheet of teacher and student activity, which was processed using simple quantitative analysis technique, mean score of motivation questionnaire and observation sheet, percentage of classical absorption and classical learning completeness. From the results of this study it can be concluded that the application of CRH learning model proved able to increase the students' motivation, activity and chemistry learning achievement to reach the minimum mastery criteria of ?75 in the third cycle. Student learning motivation increased every cycle from pre cycle up to cycle III 35,69% (low), 38,95% (low), 59,71% (medium) and 78,96% (high) respectively. The activities of teachers and students also increased each cycle in a row: teacher activity scores: 36, 38 and 38.5 with good category and student activity score: 29 (enough), 37,5 and 38 with good category. Student learning outcomes in cycle I obtained an average value of 54.3; 54.3% classical absorption and 16% classical learning completeness. In cycle II, the average score is 72.5; 72.5% classical absorption and 57.69% classical learning completeness. In cycle III, the average score is 78.76; 78.76% classical absorption and 84.61% classical learning completeness